An Autoethnographic Writer's Request to Readers. Issue 3 (November 2014) - Pelias, Ronald J.
Speaking from the position of an autoethnographic writer, I ask those who might attend to my work to adopt a number of interactional stances that I hope they will bring to our encounter. Likewise, I make several promises concerning the kind of writer I want to be. If we both agree to move forward as outlined, I argue, we will have a more productive and satisfying experience.